Battleground Berlin CIA vs. KGB in the Cold War - Murphy, David E. 1921-; Kondrašev, Sergej A. 1923-2007; Bailey, George 1919-2001 (Yale Univ. Press, 1997)
Battleground Berlin is the definitive, insider's account of the espionage warfare in Berlin between CIA and KGB from 1945 to the construction of the Berlin Wall in 1961. Two intelligence veterans - major players on opposite sides of the Cold War - have joined in an unprecedented collaboration to tell the story. Basing their narrative on personal recollections, interviews with other CIA and KGB officers, and documents never before made public, the authors provide a vast number of new details of CIA's infiltration of the new East German intelligence service; the construction, operation, and uncovering of the Berlin tunnel; and many other initiatives and countermoves dealing with the series of crises that racked Berlin and jeopardized an uneasy world peace during this period.
Keywords: Union of Soviet Socialist Republics - Komitet gosudarstvennoı̆ bezopasnosti; Soviet Union. -- Komitet gosudarstvennoĭ bezopasnosti; United States. -- Central Intelligence Agency; Sowjetunion -- Komitet Gosudarstvennoj Bezopasnosti; USA -- Central Intelligence Agency; Geschichte 1945-1962; Geheime diensten; Koude Oorlog; Außenpolitik; Politik; Cold War; Espionage, American -- Germany -- Berlin; Espionage, Soviet -- Germany -- Berlin; Spionage; Ost-West-Konflikt; Deutschland; Sowjetunion; USA; Berlin (Germany) -- Politics and government -- 1945-1990; Berlin (Germany) -- Strategic aspects; Soviet Union -- Foreign relations -- United States; United States -- Foreign relations -- Soviet Union; Berlin